Using ceres-maize model to determine the nitrogen fertilization requirements of early maturing maize in the sudan savanna of Nigeria - Adnan, A.A.; Jibrin, J.M.; Kamara, A.Y.; Abdulrahman, B.L.; Shaibu, A.S. (Informa UK Limited, 2017)
CERES-Maize model was used to determine nitrogen fertilizer requirements of early maturing maize varieties in the Sudan Savanna. Data were collected from 2013 and 2014 field experiments conducted in BUK Nigeria. The experiments consisted of 3 nitrogen fertilizer levels (0, 60, and 120 Kg N ha−1) and 2 early maize varieties (EVDT and 2009 TZEEW). Sensitivity analysis was performed to evaluate the responses of two maize to N fertilizers and for economic and strategic responses. The model predicted grain yield and harvest index reasonably well for the two varieties. Increasing N application from 0 to 30 kg N ha−1, increased grain yield by 105%, when nitrogen (N) rate was increased to 60 kg N ha−1, grain yield increased by 226%. Yield increases of 364%, 451% and 461% was observed when N rate increased from 0 to 90, 120, and 150 kg ha−1, respectively.